Effect of Hot Compression Molding Temperature Variation on Coconut Fiber HDPE Hybrid Composite and Sansevieria Trifasciata on Physical and Mechanical Properties - Muhammad Farhan Sidik; Fajar Paundra; Rene Hario Galih; Abdul Muhyi; Eko Pujiyulianto; Farid Nanda Syanur; Annisa Indah Setyawati (Journal of Industrial and Mechanical Engineering, 2024)
Temperature is one of the parameters that is very influential in the process of making HDPE matrix composites. This study aims to determine the effect of variations in heating temperature on tensile strength and bending strength and to analyze the fracture structure of HDPE composites. The materials used in this study were HDPE plastic from used bottles, coconut fiber and Sansevieria fiber with a composite ratio of 90:5:5. The process of making HDPE composites is carried out using the hot press compression method. The pressure used is 30 bar for 30 minutes. The temperature variations used are 150ºC, 160ºC, 170ºC, 180ºC, and 190ºC. This study conducted two tests, namely tensile testing and bending testing using the Universal Testing Machine. The tensile testing process uses the ASTM D 3039 standard and obtains the highest results on specimens of 170ºC with a tensile strength value of 509.80 MPa. The value of tensile strength has increased and decreased. The bending test process was carried out according to the ASTM D 790 standard and the highest results were obtained on the 170ºC specimen with a value of 90.99 MPa.